The Effect Of Work Enviroment, Work Discipline And Work Motivation On Employees' Performance At PT Bringin Gigantara Bengkulu - Sahrul Ramadhan; Sulisti Afriani; Sri Handayani (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
Work Environment, Work Discipline and Work Motivation are factors that can improve employees’ performance. The implication is that the better the work environment, work discipline and work motivation provided, the higher the employee's performance. This study aims to describe and analyze the effect of the work environment, work discipline and work motivation on employees’ performance at PT. Bringin Gigantara Bengkulu. The type of research uses descriptive quantitative. The sampling technique uses a non-probability sampling technique with a total of 51 respondents. Research analysis uses multiple linear regression analysis. Analysis results: There is a positive and significant effect between the work environment on employees’ performance at PT. Bringin Gigantara Bengkulu because tcount is greater than ttable (6.216>1.676). Therefore, H0 is rejected and Ha is accepted. There is a positive and significant influence between Work Discipline on employee performance at PT Bringin Gigantara Bengkulu because the ttable value is 1.717. Therefore, tcount is greater than ttable (4,224>1.676), then H0 is rejected and Ha is accepted, there is a positive and significant effect between work motivation on employees’ performance at PT. Bringin Gigantara Bengkulu because the ttable value is 1.717. Therefore, tcount is greater than ttable(5,082>1.676), then H0 is rejected and Ha is accepted. There is a positive and significant effect between work environment, work discipline and work motivation on employees’ performance at PT. Bringin Gigantara Bengkulu because Fcount> Ftable(60,353>3.19) with a significant value of 0.000. shows that together X1 (Work Environment), X2 (Work Discipline) and X3 (Work Motivation) have a significant influence on employees’ performance (Y) at PT. Bringin Gigantara Bengkulu. The results of the multiple regression have the equation Y=12,067+0.584(X1)+0.431(X2)+ 0.525(X3)+ e, because the direction of the regression is positive it can be interpreted that if the work environment, work discipline and work motivation increase then performance employees at PT Bringin Gigantara Bengkulu will also increase.